POLA ASUH ANAK DI PKBM FATMA VISI SUKSES KELURAHAN TANGKERANG TENGAH KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Retno Larasati; Said Suchil Achmad; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by problems that occur in the filed, namely (1) Students PKBM Fatma Vision Success consist of children of drugs, neglected childeren and street children (2) Parents pay less attention to children’s learning activities (3) There are still parents who letting the child behave at will when the child makes a mistake, so the parent more often tekes the attitude does not care about the child’s attitude. The research method used is descriptive research with quantitaive apporoach. It is planned to be implemented since February 2018 at PKBM Fatma Visi Sukses. The results showed that the indicator of permissive parenting is the most dominant applied by parents. The indicators of authoritarian parenting are quite high. And the lowest is the democratic parenting. Where parents are lacking in parenting at home.Keywords: Foster Pattern, Child